Midwives' compliance with post-exposure prophylaxis guidelines in Tshwane District, South Africa - Mosehle S. Matlala; Thanyani G. Lumadi (AOSIS, 2024)
Background: Human immunodeficiency virus (HIV) remains a major public health concern. Midwifery practitioners as frontline healthcare workers (HCWs) remain susceptible to occupational exposure to infections while performing their routine duties. It is estimated that 90% of occupational exposures occur because of a lack of awareness and training regarding prevention and measures to be taken in case of accidental exposure. Objectives: The study aimed to assess the knowledge, attitudes and compliance of midwifery practitioners regarding post-exposure prophylaxis (PEP) guidelines. Method: Concurrent mixed-methods research approach with qualitative nested in quantitative design was followed. A random simple sampling technique was used to collect quantitative data from 71 midwifery practitioners. Simultaneously, a purposive non-probability sampling technique was used for the qualitative approach with two occupational health and safety (OHS) practitioners and 13 midwifery practitioners. Data were collected through questionnaires and semi-structured interviews. Quantitative data were analysed with SPSS version 24 and presented in tables and figures, and thematic analysis was employed for the qualitative strand. Results: The midwifery practitioners have good knowledge about PEP for HIV. However, the study revealed the underreporting of accidental exposures to blood and body fluids (BBFs) and the underutilisation of available PEP services. Conclusion: Maternity units are high-risk clinical environments. Underreporting of incidents of exposure remains prevalent among midwifery practitioners. Contribution: The findings will inform policy development structures and hospital management regarding knowledge and implementation gaps related to PEP guidelines in the specific hospitals. Strategies to improve compliance with PEP among midwifery practitioners were developed as a derivative from study findings.